Confucian Entrepreneurship: Towards a Genealogy of a Conceptual Tool - Smith, Andrew; Kaminishi, Miriam (Journal of Management Studies, 2019)
The concept of the ‘Confucian Entrepreneur’ is now used by many scholars to understand entrepreneurship in China and other East Asian countries. This paper traces the development of this concept from its roots in the writings of nineteenth‐century Western authors to its use in modern management journals. We show that while this conceptual tool has been adapted over time, the claims associated with it have remained largely similar. Use of the term Confucian entrepreneur implies belief that Confucian ideas induce Chinese entrepreneurs to behave differently than their Western counterparts, a claim for which the empirical foundations are weak. We do not go so far as to say that those who research Chinese entrepreneurship should discard the concept of the Confucian entrepreneur simply because of its historical origins in colonialism. However, we do call on researchers to reflect on the historical origins of their conceptual tools. By historicising our theories of entrepreneurship, this paper should encourage greater scholarly reflexivity and thus the development of entrepreneurship and management theory with greater predictive power.